WHAT SUPPORT WORKERS NEED TO KNOW ABOUT DYSLEXIA: A STUDY OF THE CAUSES, FACTORS AND INFLUENCES ON DYSLEXIA - Bharat, Anagha (2010)
This piece of research is a desk-based study reviewing past literature on the causes, characteristics and influences of specific learning disabilities, namely dyslexia. This current study is introduced by presenting three case snippets collected from special educators and parents of dyslexic children from India. Confidentiality has been maintained throughout this work by omitting names of all institutions and using only the initials of people. The issue of ‘what is dyslexia’ is considered in the introduction. This is followed by an overview of the causes behind dyslexia where the causal modelling framework is discussed. Here the biological, cognitive and environmental factors are looked into. The social and emotional consequences of dyslexia are presented in the next chapter. In this section, the two most important dimensions of self-concept and self-esteem have been critiqued. In addition, studies relating to emotional problems of a more severe psychological nature are also evaluated. This is followed by the discussion on the importance of support for dyslexics and how support can be provided. The study concludes with implications of current policies on inclusion and what it means to be living with dyslexia.